THE EFFECT OF HEALTH EDUCATION ON CHILDBIRTH PROGRAM AND PREVENTION OF COMPLICATIONS USING WA GROUP ON THE ATTITUDE OF THIRD TRIMESTER PREGNANT WOMEN AT SRENGAT HEALTH CENTER IN PREPARATION FOR CHILDBIRTH - Dwi Lukmawati; Fransiska Septiana S; Lailaturohmah (EZRA SCIENCE BULLETIN, 2023)
MMR in Indonesia is still high, mostly caused by direct causes, namely bleeding, infection, eclampsia, long labor and abortion in addition, maternal mortality is also motivated by low levels of knowledge, attitudes, education, parity, age too young to give birth, giving birth too often, too old to give birth, so it is necessary to prepare for childbirth, but in fact there are still many mothers who are not ready to face childbirth, so there is a need for education, one of which is through the WA group. This type of research uses experimental quasy with a research design, namely Nonequivalent Control Group Design. The population in this study is all III trimester pregnant women who are at the Srengat Health Center for the February 2023 period as many as 82 pregnant women. The sampling technique uses a formula for estimating the sample size of 20 people. Measuring instruments using SAP and questionnaires. Data analysis using the Mann Whitney test. The description of the attitude of pregnant women in the third trimester before education using the WA group had an average value of 37.10, after intervention an average value of 64.60. The description of the attitude of pregnant women in the third trimester before education using leaflets has an average value of 36.00, after intervention the average value is 53.65. There are differences in the attitudes of third trimester pregnant women in preparation for childbirth between those given health education for the Childbirth Planning and Prevention of Complications Program using the WA group and leaflets at the Srengat Health Center in 2023 with a significant value of p value of 0.000. Providing education using WA Group is more effective than leaflets because Whatsapps social media is easy to use to improve mothers' attitudes towards childbirth preparation because through WA Group can provide information and discussion about childbirth preparation rather than leaflets. Eeducation using WA group is more effective in improving the attitude of mothers in preparation for childbirth.